The study on the awareness of the army quarter’s occupants on adopting the concept of ‘culture of maintenance’ to enhance the quality of maintenance services - Abu Hassan, Roslan (1999)
The Malaysian’s economic downturn since the years 1997 has resulted in severe contraction in growth in almost all-economic sector. The construction sector is one of the hardest hits. It is worst still during the time of recession, the first to be cut from an allocation both in private or government sectors are that of the maintenance budget. The study on the awareness of the army quarter’s occupant on adopting the concept of ‘Culture of maintenance’, would change their mindset and attitude instead solely dependent on JKR Maintenance Unit in maintaining the quarter, they proactively taking proper and careful use of facilities in order to prolong the life span of the building quarters. Thus by having good maintenance culture among the quarters dweller it will ensure that asset will be maintain with minimal cost and at longer life span. The roles of JKR Armed Forces under the Maintenance Unit need to change in this time of crisis. More ‘stressing’ is needed to a finer tune on both the procedures and work culture in order to give a better service to Quarters Dweller. By proactively, providing quality maintenance services it would create a harmonious link between both parties, JKR as a service provider and quarters occupant as the honored customer.